Prevalence of type 2 diabetes and its associated factors among general population of Pokhara Metropolitan City - Shrestha, Neelam; Vaidya, Gemorina (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Diabetes mellitus is emerging as a major public health problem in Nepal. This study aimed to assess the prevalence of type 2 diabetes and its associated factors among the general population of Pokhara Metropolitan City. Methods: A community-based cross-sectional study was conducted from August 2018 to October 2019, involving a total of 617 participants aged 30 to 90 years in Pokhara Metropolitan. Participants were selected using a systematic random sampling technique. Data were collected using face-to-face interviews from consented participants. Data analysis was done using SPSS 20.0. Descriptive statistics, chi-square tests, and binary logistic regression were utilized. The level of significance was set at a p-value < 0.05. Results: The overall prevalence of type 2 diabetes was 112(18.2%), with 58(19.4%) among males and 54(17%) among females. Out of the participants with diabetes, 54(48.2%) were newly identified by the study. Older age, illiteracy, physical inactivity, family history of diabetes, known cases of hypertension, alcohol consumption, and obesity were found to be significantly associated with type 2 diabetes. Conclusions: The study revealed a relatively higher prevalence of type 2 diabetes. Interventions on promoting physical activity, controlling alcohol consumption, maintaining body weight, and controlling hypertension may help in the prevention of diabetes among the study population. It shows there is an urgent need for community awareness programs focusing on the disease and its risk factors.